LncRNA–miRNA–mRNA ceRNA network of different body colors in Plectropomus leopardus - Hao, Ruijuan; Zhu, Xiaowen; Tian, Changxu; Jiang, Mouyan; Huang, Yang; Li, Guangli; Zhu, Chunhua (Frontiers in Marine Science, 2023)
Long noncoding RNAs (lncRNAs) play a multifaceted role in transcriptional regulation and the potential molecular regulatory mechanisms of lncRNAs and lncRNA-miRNA-mRNA networks in body color formation is of great significance for its selective breeding. Therefore, lncRNAs of red- and black-colored Plectropomus leopardus were identified and analyzed. Sequencing analyses identified 167 differentially expressed lncRNAs (DELs) between red- and black-colored P. leopardus, including 89 upregulated and 78 downregulated DELs in the red-colored group (FDR<0.05 and |log2FC|>1). Differentially expressed miRNAs (DEMs), genes (DEGs) and DELs analysis found 605 and 125 negatively co-expressed miRNA-mRNA pairs and lncRNAs-miRNA pairs, respectively. Further correlation analysis with Spearman's correlation coefficient >0.9 as the threshold identified 3721 lncRNA-mRNA pairs. Then, a competitive endogenous RNA (ceRNA) network of 325 pairs (p<0.05) was obtained. GO and KEGG pathway enrichment of network DEGs showed that melanin metabolic process, lipid metabolism, and immune-related pathway were enriched. The ceRNA network provided interactions among lncRNAs, miRNAs, and mRNAs and extended the molecular foundation of body color formation.